Efeitos agudos do treinamento respiratório e resistido com restrição de fluxo sanguíneo sobre variáveis respiratórias, hemodinâmicas e força muscular periférica em sujeitos com DPOC - Santos, Camila Fernandes Pontes dos (2024)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a chronic limitation of airflow that presents dyspnea and reduced functional capacity. To this end, inspiratory muscle training (IMT) and resistance training (RT), with blood flow restriction, appear to improve muscle strength and functional performance. Objective: To evaluate the acute effects of respiratory and resistance training with blood flow restriction on respiratory variables, hemodynamics and peripheral muscle strength in subjects with COPD. Methodology: The sample consisted of 14 subjects (67.50 ± 1.76 years; 67.67 ± 3.39 kg; 1.58 ± 0.02 m; 26.88 ± 1.28 kg/m2), with mild, moderate or severe COPD, who participated in the 3 experimental protocols, with a wash-out 48h-72h, randomly: 1) RT with low-load (30% 1RM) + IMT (30% MIP); 2) RT with low-load + blood flow restriction/50% of arterial occlusion pressure (AOP) + IMT and 3) TR with moderate load (50% 1RM) + IMT (50% MIP). The assessment consisted of: body composition, Ankle-Brachial Index (ABI), determination of OAP, assessment of inspiratory strength, dynamometry and 1RM test. The following variables were recorded: maximum inspiratory pressure (MIP) and muscle strength (MS), previously during the assessment and after each session; in addition to heart rate (HR); respiratory rate (RR), blood pressure (BP), peripheral oxygen saturation (SpO2), subjective perception of exertion (SPE) and dyspnea, at the moments: before, immediately after and 10 minutes after the sessions. SPSS (26.0) was used for statistical analysis and, to verify the normality, homogeneity and sphericity of the data, the Shapiro-Wilk, Levene and Mauchly tests, respectively. One-Way Anova was used for parametric data, followed by Tukey's post-hoc, and repeated measures, followed by Bonferroni's post-hoc, and for non-parametric data, Friedman's Anova test was used, followed by the Wilcoxon test. The Pearson test was also performed to correlate POA and Pimax, adopting a significance level of P ≤ 0.05. Results: There was a significant reduction in SBP (P < 0.01), HR (P < 0.05), RR (P < 0.05) and dyspnea (P < 0.05) in the protocols at moment 10' and an increase in RR, immediately after, in LLRT+IMT (P < 0.01) and MLRT+IMT (P < 0.05); dyspnea in LLRT+BFR+IMT (P < 0.05) and MLRT+IMT (P < 0.01), and SpO2 in the protocols (P < 0.01), however, only LLRT+BFR+IMT showed a hypotensive effect on DBP (P < 0.05). There was also a significant increase in SPE (P < 0.05) in protocols and training; the peripheral strength of upper limbs and lower limbs (P < 0.01) in the protocols; and inspiratory strength, only in LLRT+BFR+IMT (P < 0.01), but there was no correlation between OAP and MIP (P > 0.05). Conclusion: IMT associated with TR, with or without BFR, promoted a hypotensive effect on SBP and decreased HR; RR and dyspnea, in addition to increases in SpO2, peripheral and respiratory muscle strength, and SPE, in all protocols analyzed; however, LLRT+BFR+IMT was more effective as it was the only one to present an increase in inspiratory strength and a hypotensive effect at DBP.